PENGARUH PENERAPAN PRINSIP GOOD GOVERNANCE TERHADAP PENERIMAAN WAKAF TUNAI - Fahma As’har; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTWaqf is the implementation of the development of waqf, which is carried out by collecting cash waqf certificates issued by Islamic financial institutions. Optimizing collection and management of waqf requires good governance, therefore Good Governance is believed to be a benchmark for the good or not of an organization's performance. The purpose of this study is to find out whether there is an influence of the application of the principle of good governance to the acceptance of cash waqf and how much influence the application of the principle of good governance to the acceptance of cash waqf. The methodology used is a quantitative method with a survey approach. The results of the research show that the application of the principles of good governance has a significant effect on the level of acceptance of cash waqf. Research that was only conducted in 10 waqf management institutions made the diversity of opinions from other waqf management institutions not yet concluded properly.Keywords: Good governance, nazhir, and cash waqf.